Direct visualization-guided endoscopic management of complex colonic diverticular disease: a proof-of-concept case series - Tianjie Han; Junshan Li (Frontiers in Medicine, 2026)
Background Complex colonic diverticular disease, including diverticular bleeding, inflammatory diverticular disease, presents substantial therapeutic challenges for conventional colonoscopy because of limited intradiverticular visualization, difficult access, and restricted maneuverability. Failure to precisely localize the culprit lesion or inflammatory nidus may lead to recurrent symptoms, delayed treatment, or surgical intervention. The EyeMax direct visualization system, originally designed for pancreatobiliary interventions, may provide a novel strategy for targeted intradiverticular diagnosis and therapy. Aim To evaluate the feasibility, safety, and potential clinical applications of the EyeMax direct visualization system in the endoscopic management of complex colonic diverticular disease. Methods We conducted a retrospective proof-of-concept case series of patients with complex colonic diverticular disease who underwent EyeMax-assisted endoscopic intervention at a tertiary hospital between January 2024 and July 2026. Included patients had diverticular bleeding, diverticulitis with localized inflammation or purulent cavity, or diverticular fecalith incarceration. Primary outcome was technical success, defined as successful intradiverticular access and completion of intended intervention under direct visualization. Secondary outcomes included clinical success, adverse events, recurrence, and need for surgery. Results Seven patients were included, comprising diverticular bleeding ( n = 2), inflammatory diverticular disease( n = 5). EyeMax-assisted intervention achieved a technical success rate of 100% (7/7). Clinical success was achieved in 85.7% (6/7) of patients. Among the five patients with inflammatory diverticular disease, direct intradiverticular exploration identified purulent cavities and inflammatory debris in all cases, with impacted fecaliths detected in three patients. Four patients improved following direct visualization-guided lavage with or without fecalith extraction, whereas one patient with severe diverticulitis complicated by abscess formation required surgical intervention. No procedure-related perforation, delayed bleeding, infection, or mortality occurred. During follow-up ranging from 1 month to 2 years, no recurrent bleeding or inflammatory events were observed. Conclusion In this preliminary assessment, the EyeMax system demonstrates feasibility for managing complex colonic diverticular disease, with potential utility in diverticular bleeding, diverticulitis, and fecalith incarceration. These findings are preliminary, and the concept of direct visualization-guided precision endoscopy warrants validation in larger prospective multicenter studies.